Modelling of hybrid rocket flow-fields with computational fluid dynamics - Ismail, Izham Izzat; Rozainuddin, Nur Husnina Aufa; Nordin, Norhuda Hidayah; Azami, Muhammad Hanafi (Semarak Ilmu Publishing, 2022)
A low regression rate is a major limitation in the hybrid rocket propulsion system. This paper is to study the regression rate characteristics of a cylindrical solid grain with cryogenic propellants. Paraffin (P) fuel is coupled with two types of oxidizers, namely gaseous oxygen (GOX) and nitrous oxide (N2O). ANSYS software is used as the CFD platform to observe the hybrid rocket flow-fields. The modelling values obtained from the pressure, temperature, velocity, and wall heat flux contours are used to calculate the hybrid rocket performance in terms of regression rate, thrust, specific impulse, characteristic velocity, and exit Mach number. The numerical results show that the mass-flow-inlet boundary conditions, initial design feature, and type of propellant play an important role in the enhancement of hybrid rocket performance. Result shows that enhanced of 68 % of the regression rate, 59 % of thrust, 6 % of specific impulse and exit Mach number, and % of characteristic velocity by improved 50% of mass flow rate. Due to the high flame temperature, the GOX/P propellants produce the best hybrid rocket motor compared with the others.